Model-model evaluasi pendidikan - rohmad qomari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
On learning literature, there many kind of learning model design, for example model developed by Winarno Surakhmad, Winkel, Hisyam Zaini et al., Briggs and Wager, Gerlach and Ely, and Kemp. Those models design have component and pattern that different each other, from model that have dominant quantitative measure like measurement model and model that using qualitative approach as illuminative model. By studying many models and broaden view not only to one model approach, and even combine (merger) between two or more models, or even developing our specific model. As one basic rule, good evaluation have to comply with several principle, namely validity, reliability, objectivity, continuity, and comprehensive so the resulted information can became source to make right and wise decision. On learning literature, there many kind of learning model design, for example model developed by Winarno Surakhmad, Winkel, Hisyam Zaini et al., Briggs and Wager, Gerlach and Ely, and Kemp. Those models design have component and pattern that different each other, from model that have dominant quantitative measure like measurement model and model that using qualitative approach as illuminative model. By studying many models and broaden view not only to one model approach, and even combine (merger) between two or more models, or even developing our specific model. As one basic rule, good evaluation have to comply with several principle, namely validity, reliability, objectivity, continuity, and comprehensive so the resulted information can became source to make right and wise decision. Keywords: evaluation, learning, measurement model, illuminative model.